Corporate information management and use in 2011 - Bustelo-Ruesta, Carlota (Anuario ThinkEPI, 2012)
Information technologies determine three trends in the management and use of information in companies: corporate transparency, competitive intelligence and use of social media or web 2.0. Corporate transparency, an unstoppable trend despite the economic crisis, affects records management. Competitive intelligence is gathering momentum in some sectors and enterprises, while still not widespread in small and medium-sized enterprise (SMEs) in Spain. When companies embrace the use of social media or web 2.0, this begins to transform their management and use of information.
Keywords: Information management; Private sector; Corporate transparency; Corporate social responsibility; Records management; Competitive intelligence; Web 2.0; Social media.